2001
DOI: 10.1001/archotol.127.11.1331
|View full text |Cite
|
Sign up to set email alerts
|

Superior Canal Dehiscence

Abstract: Fenestration of the superior canal rendered all superior canal afferents sensitive to pressure, whereas less than half of the other afferents became pressure sensitive. The direction of the superior canal afferent responses agreed with the predictions of our model of endolymph flow within the superior canal. A rigid seal applied to the fenestra abolished pressure sensitivity while maintaining physiologic rotational sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Experimental evidence reported previously demonstrate that a dehiscence in the superior canal can also increase sound-evoked responses in the horizontal canal and otolith organs 8 , 11 , 36 38 . Present results indicate this occurs through the same two mechanisms that affect the dehisced canal – vibration delivered by waves, and wave pumping of endolymph.…”
Section: Discussionmentioning
confidence: 83%
“…Experimental evidence reported previously demonstrate that a dehiscence in the superior canal can also increase sound-evoked responses in the horizontal canal and otolith organs 8 , 11 , 36 38 . Present results indicate this occurs through the same two mechanisms that affect the dehisced canal – vibration delivered by waves, and wave pumping of endolymph.…”
Section: Discussionmentioning
confidence: 83%
“…As a result of a dehiscence in the otic capsule, inner ear biomechanics are altered, such that low-frequency acoustic stimuli of high intensities may create a traveling wave toward the dehiscence, stimulating the vestibular end organs (3, 24). This shunting of acoustic energy creates both a distortion to sound perception, causing hyperacusis and reverberation, and sound- and pressure-evoked vertigo and dizziness (10, 25). …”
Section: Etiologymentioning
confidence: 99%
“…Dehiscence of bone over the superior semicircular canal is the pathologic basis for this syndrome and has been verified in a surgically created animal model of the disorder . Although there have been 3 published reports of acquired dehiscence due to erosion from a neoplasm or osteomyelitis, for all other cases the cause of the dehiscence remains unknown.…”
Section: Introductionmentioning
confidence: 92%
“…Dehiscence of bone over the superior semicircular canal is the pathologic basis for this syndrome and has been verified in a surgically created animal model of the disorder. 2 Although there have been 3 published reports of acquired dehiscence due to erosion from a neoplasm or osteomyelitis, [3][4][5] for all other cases the cause of the dehiscence remains unknown. A recent study 6 found that patients with radiographic superior canal dehiscence were more likely to have had a higher mean body mass index (BMI) (calculated as weight in kilograms divided by height in meters squared) and history of obstructive sleep apnea compared with those without dehiscence.…”
mentioning
confidence: 99%